Effect of Fetal Liver Cryopreserved Cells on Survival, State of Prooxidant-Antioxidant and Monooxigenase Systems of Rats During Ageing - Ochenashko, O. V.; Nikitchenko, Yu. V.; Sheremet, A. A.; Petrenko, A. Yu. (Problems of Cryobiology and Cryomedicine, 2008)
The effect of a long-term introduction of cryopreserved fetal liver cells (FLCs) on dynamics of some indices of blood prooxidantantioxidant system, state of liver monooxigenase system and survival of rats during ageing, has been studied in the research. Multiple injections of FLCs to rats under ageing were established to increase their survival rate, to decrease the level of LPO products and augment the reliability of prooxidant and monooxigenase systems. These data enable considering the FLCs as a perspective way to correct the age-related changes.